An Online Survey of the Dietary Practices of Saudi Students in the UK: A Quantitative Study - Abu Qurain, Ali M; Al Turki, Fatimah A; Hall, Jason; Alzain, Hassan M; Mitchell, Graeme; Leavey, Conan (Journal of Agri-Food Science and Technology, 2023)
There has been an abundance of research on the dietary practices of international university students in the United Kingdom (UK), as they comprise a significant proportion of the country’s undergraduate population. However, there is a paucity in the literature with regard to the dietary practices, or other health behaviours, of Saudi students studying in the UK. Therefore, this empirical study sought to provide new insights to address this gap. This study contribution to investigate the dietary practices of Saudi students in the UK. The data was collected from a sample of 212 university students and encompassed an age range from 18 to 31+ years. A quantitative methodology was adopted in the form of an exploratory survey questionnaire. The sample was recruited through voluntary and snowball sampling techniques. Questionnaire data was analysed using Microsoft Excel and SPSS for Windows, version 26. The results demonstrated that various intrapersonal, interpersonal, and environmental factors play a significant role in developing eating behaviours and dietary choices. Some favourable changes in dietary practices were observed among Saudi students in the UK as opposed to Saudi Arabia, including a higher intake of fruit and vegetables, along with a lower intake of soft drinks, sugary and fatty foods. However, there was a notable reduction in consumption of all types of meat and fish as well as the total number of daily meals. Additionally, around a third of participants regularly consumed ready-to-eat food and takeaways 2-6 times a week. Interventions should therefore consider individual, societal and environmental factors.